Detailing for acoustics - Lord, Peter 1953-; Templeton, Duncan (Spon, 1996)
This revised and updated edition of a well-established manual includes considerable improvements for easier and more accessible use of the information: detail sheets have been rearranged under new headings, graphics have been improved and acoustic performance data expanded. The authors also give advice on the appropriate materials and assemblies